Propuesta de mejora del sistema de tratamiento de aguas residuales de la empresa Somos K S.A. (2018)
The present work of degree develops a proposal of improvement for the system of treatment of the residual water of the company SOMOS K S.A. in the WWTP because resolution 0631 of 2015 is prohibited. The possible problems of operation and maintenance of the WWTP were determined and analyzed, taking into account these analyzed parameters and through bibliographic information, 3 improvement alternatives were proposed that allow reducing the pollutants that do not comply with the regulations. The design of the grease trap unit is proposed by means of 3 alternatives, by means of a selection matrix, the best alternative was chosen according to the needs of the company. Once the alternative of improvement was chosen, the experience was carried out, taking into account the step by step that contemplates the stages of coagulation, flocculation and sedimentation. This treated water is sent to perform the respective characterization, in this way the decrease in the problem parameters is determined.